Synthesis of 3D Hexagram-Like Cobalt–Manganese Sulfides Nanosheets Grown on Nickel Foam: A Bifunctional Electrocatalyst for Overall Water Splitting - Li, Jingwei; Xu, Weiming; Luo, Jiaxian; Zhou, Dan; Zhang, Dawei; Wei, Licheng; Xu, Peiman; Yuan, Dingsheng (Nano-Micro Letters, 2017)
The exploration of low-cost and efficient bifunctional electrocatalysts for oxygen evolution reaction and hydrogen evolution reaction through tuning the chemical composition is strongly required for sustainable resources. Herein, we developed a bimetallic cobalt–manganese sulfide supported on Ni foam (CMS/Ni) via a solvothermal method. It has discovered that after combining with the pure Co9S8 and MnS, the morphologies of CMS/Ni have modulated. The obtained three-dimensionally hexagram-like CMS/Ni nanosheets have a significant increase in electrochemical active surface area and charge transport ability. More than that, the synergetic effect of Co and Mn has also presented in this composite. Benefiting from these, the CMS/Ni electrode shows great performance toward hydrogen evolution reaction and oxygen evolution reaction in basic medium, comparing favorably to that of the pure Co9S8/Ni and MnS/Ni. More importantly, this versatile CMS/Ni can catalyze the water splitting in a two-electrode system at a potential of 1.47 V, and this electrolyzer can be efficiently driven by a 1.50 V commercial dry battery. Highlights: 1 Cobalt–manganese sulfides grown on Ni foam (CMS/Ni) with three-dimensionally hexagram-like nanosheets structure were prepared via a solvothermal method. 2 As-prepared CMS/Ni shows highly catalytic activity for OER and HER in basic medium and can catalyze water splitting by a 1.50 V dry battery.